Photochemically Assisted LC–MS Method Development and Validation for Stability-Indicating Determination of Glasdegib in Rat Plasma - Satya Venkata Sumaltha Sagi; Usharani Mandapati; Bharathi Dommeti; Rameshraju Rudraraju (International Journal of Photochemistry and Photochemical Research, 2026)
A simple, precise, and cost-effective LC–MS method was successfully developed for the determination of Glasdegib in rat plasma. The method optimization was carried out by systematically varying key chromatographic parameters, including flow rate, injection volume, analyte concentration, and mobile phase composition, to achieve optimal sensitivity and resolution. A C18 Hypersil BDS column (150 mm × 4.6 mm, 3.5 µm particle size) was used for chromatographic separation, offering effective peak shape and repeatability. The mobile phase consisted of a mixture of acetonitrile and 0.1% formic acid in the ratio of 30:70 (v/v), ensuring proper ionization and improved analyte response. The flow rate was maintained at 0.7 mL/min, allowing adequate interaction between the analyte and stationary phase while minimizing analysis time. Detection was carried out at a wavelength of 250 nm, where Glasdegib exhibited significant absorbance, enhancing method sensitivity. Under these optimized conditions, Glasdegib showed a retention time of 3.115 minutes, indicating a rapid and efficient analytical run suitable for high-throughput analysis. By assessing metrics including linearity, accuracy, precision, specificity, and robustness, the created approach was validated in compliance with accepted practices. With high correlation values, the data showed outstanding linearity over the chosen concentration range. Studies on accuracy and precision verified the method's dependability and repeatability. Overall, the proposed LC–MS method is robust, rapid, and economical, making it highly suitable for routine quantitative analysis of Glasdegib in bulk drug substances, pharmaceutical formulations, and biological samples such as rat plasma.
Keywords: Benzimidazole; Glasdegib; LCMS; formulation design; method development and validation